2014
DOI: 10.5059/yukigoseikyokaishi.72.1228
|View full text |Cite
|
Sign up to set email alerts
|

The Asymmetric Catalytic Mannich Reaction Catalyzed by Organocatalyst ^|^mdash; A Personal Account ^|^mdash;

Abstract: Abstract:The Mannich reaction is a synthetically useful method for the construction of nitrogen containing molecules. Organocatalysts have been successfully applied to the Mannich reaction. Our group has been engaged in research on the organocatalyst mediated Mannich reaction since the early days of its development in 2002. We have developed a proline mediated three component Mannich reaction of aldehyde, ketone and p anisidine under the high pressure induced by water freezing. Proline was found to effectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 123 publications
0
5
0
Order By: Relevance
“…6 With the development of reliable, often benchtop instruments the applications of HHP in synthetic chemistry have expanded. The more recent examples include hydrogenation, 7 the addition of enamines to Michael acceptors, 8 enantioselective Mannich reactions, 9 lipase-catalyzed esterification, 10 diastereoselective asymmetric nitro-aldol reaction, 11 Michael, 12 and aza-Michael reactions, 13,14 Diels–Alder reactions, 15 and Friedel–Crafts alkylation of indoles. 16 Despite the promising developments, high pressure synthesis is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…6 With the development of reliable, often benchtop instruments the applications of HHP in synthetic chemistry have expanded. The more recent examples include hydrogenation, 7 the addition of enamines to Michael acceptors, 8 enantioselective Mannich reactions, 9 lipase-catalyzed esterification, 10 diastereoselective asymmetric nitro-aldol reaction, 11 Michael, 12 and aza-Michael reactions, 13,14 Diels–Alder reactions, 15 and Friedel–Crafts alkylation of indoles. 16 Despite the promising developments, high pressure synthesis is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of our interest in asymmetric synthesis of name reactions, [16–26] in this review, we wish to highlight the recent developments achieved and reported in asymmetric Mannich reaction. It is worthy to mention that the application of asymmetric organocatalyzed‐Mannich reaction in the total synthesis of naturally occurring compounds and heterocycles as power tool, has been extensively reviewed [4,27–43] …”
Section: Introductionmentioning
confidence: 99%
“…6 However, in recent asymmetric reactions, catalytically generated enamines are essentially the key intermediates. In this context, chiral secondary and primary amines act as catalysts for the a-functionalization of ketones in bond forming reactions such as the aldol reaction, 3,7 Mannich reaction, 3,8 Michael reaction, 3 a-aminoxylation 3 and a-aminations. 3 In the Mannich reaction of acetone catalysed by a primary amine-thiourea organocatalyst, an enol mechanism was proposed, 9 while an enamine mechanism is proved by calculation and 13 C kinetic isotope effects in the Michael reaction of acetone catalysed by a similar catalyst.…”
Section: Introductionmentioning
confidence: 99%